Ecosophy at the End of Nature - Cavazza, Elisa (The Trumpeter, 2015)
Naess’s ecosophy is one of the first and most influential philosophical formulations of relationism and environmental ontology. In this paper, I argue that his proposal can be re-analysed in light of Latour’s recent political ecology. The comparison unfolds through Latour’s direct criticisms of Naess in the central concepts of objectivity, politics, anthropcentrism, ecological crisis, morality, facts and values. On one hand, the comparison offers material to rework the potentials and pitfalls of a perspective that understands the ecological crisis in terms of necessity to reopen the concept of nature and of the human. On the other hand, Latour exposes some of Naess’s fundamental ambiguities. I argue that precisely in these ambiguities lies Naess’s fecundity and, maybe, the possibility for ecosophy to rephrase its tenets today.